2001
DOI: 10.2527/2001.793574x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of undegraded intake protein on reproductive performance of primiparous beef heifers maintained on stockpiled fescue pasture.

Abstract: The objectives of this study were to evaluate the effects of pre- and postpartum undegraded intake protein (UIP) supplementation on body condition score (BCS), BW, calf weight, milk production, serum IGF-I concentrations, and postpartum interval in primiparous beef heifers (n = 44). Heifers were maintained on endophyte-free stockpiled tall fescue (11.7% CP, 38% ADF) and individually fed supplement daily beginning 60 d prepartum. Pre- and postpartum supplements provided 19.3% CP, 83.4% TDN (UIP); 14.1% CP, 84.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…Furthermore, forage DMI was similar (P = 0.45) regardless of supplement type, comparable to findings in the current study. However, Strauch et al (2001) reported heifers offered stockpiled tall fescue forage (11.7% CP) had increased prepartum forage DMI when heifers were supplemented with an additional 84 g/d (106 vs. 190 g/d) RUP for 64 d prior to calving compared with control heifers.…”
Section: Individual Feeding Resultsmentioning
confidence: 96%
“…Furthermore, forage DMI was similar (P = 0.45) regardless of supplement type, comparable to findings in the current study. However, Strauch et al (2001) reported heifers offered stockpiled tall fescue forage (11.7% CP) had increased prepartum forage DMI when heifers were supplemented with an additional 84 g/d (106 vs. 190 g/d) RUP for 64 d prior to calving compared with control heifers.…”
Section: Individual Feeding Resultsmentioning
confidence: 96%
“…Evidence of the effect of supplementation on post-partum reproductive performance has been equivocal. Delcurto et al (1990) and Strauch et al (2001) both showed little evidence for a decreased calving interval associated with protein supplementation, but Beaty et al (1994) and Sasser et al (1988) showed that increasing the crude protein (CP) Unfortunately, these studies do not represent long-term supplementation programmes or characterize variable stocking rates common to production systems in Mediterranean climates. We hypothesized that supplementation based upon body condition will result in similar performance to that with supplementation based upon forage availability and quality.…”
Section: Introductionmentioning
confidence: 99%
“…Although limited, research investigating the effects of UIP supplements on endocrine responses indicates UIP supplements may alter metabolic (Sletmoen-Olson et al, 2000b;Kane et al, 2004;Reed et al, 2007) and reproductive (Strauch et al, 2001;Kane et al, 2004) endocrine patterns. Interestingly, Sletmoen-Olson et al (2000a) reported that calf birth weights were greater for cows fed moderate levels of UIP compared with those fed low or high amounts of UIP.…”
Section: Degradable and Undegradable Intake Proteinmentioning
confidence: 99%